Extended framework for the analysis of innovative Smart City business models - Ángel F. Agudo-Peregrina; Julio Navío-Marco (International Telecommunications Society (ITS), 2016)
Besides the promising forecasts for Smart City market, many projects haven't taken off due to financial restrictions, unsustainable business models or too technological visions instead of citizen orientation. The need for innovative business models in the context of Smart City motivates this study, that first reviews the Smart City business model literature, and then proposes a framework to study several companies within each sector of a broad definition of the Smart City. The results of the analysis show that there is a need to build a holistic framework to analyze all business models included in the Smart City. They also suggest that policy makers should extend their vision of the Smart City, and include a large group of innovative businesses that, using disruptive technologies, are creating deep impacts on citizens' lives.
Keywords: 330; smart city; business model; innovation; services